Anisotropy Spectra of the Solvent-Sensitive Fluorophore 4-Dimethylamino-4′-Cyanostilbene in the Presence of Light Quenching(1) - Gryczynski, Ignacy (J Fluoresc, 1998)
We examined the emission wavelength-dependent anisotropies of the solvent-sensitive fluorophore 4-dimethylamino-4′-cyanostilbene (DCS) under conditions of light quenching by polarized time-delayed quenching pulses. Illumination on the long-wavelength side of the emission spectrum with time-delayed light pulses resulted in a progressive decrease in the emission anisotropy as the observation wavelength increased toward the stimulating wavelength. The anisotropy changes of DCS were most wavelength dependent when spectral relaxation occurred during the excited-state lifetime. Light quenching of DCS in a low-viscosity solvent revealed no wavelength-dependent anisotropies. Control measurements using a solvent-insensitive fluorophore did not show any wavelength-dependent anisotropy with light quenching. The data for DCS can be explained by a model which allows wavelength-selective quenching of the long-wavelength emission formed by time-dependent spectral relaxation. These results indicate that polarized light quenching can be used to study systems which display multiple emissions and/or time-dependent spectral shifts.